A review Echinomycin: A Journey of Challenges - Lafi, Zainab; Alshaer, Walhan; Hatmal, Ma’mon M.; Zihlif, Malek A.; Asha, Nisreen Y.; Abdelnabi, Hiba; Awidi, Abdullah (Jordan Journal of Pharmaceutical Sciences, 2023)
Echinomycin is a natural compound discovered and isolated from bacteria, introduced as a promising antibiotic and anticancer therapy. However, it failed clinically due to improper formulations and a short half-life. After the unsuccessful clinical trials, echinomycin was overlooked. Recently, a new mechanism of action has given some hope for reviving echinomycin as an inhibitor of hypoxia-inducible factor (HIF-1). In 2015, echinomycin received orphan drug designation for treating acute myeloid leukemia in the USA. Furthermore, advancements in drug delivery systems have provided new prospects to overcome the echinomycin formulation issues and explore further therapeutic benefits. This review details the echinomycin journey along with the main challenges of this potent drug and provides insights into possible future clinical applications.